The Relationship Between Flat Foot and Dynamic Balance in Basketball Players - Chattalia, Vida Nanda (International Journal of Public Health Excellence (IJPHE), 2024)
Basketball players always engage in highly mobile physical activities that need to be supported by normal foot anatomy. Most important parts influencing musculoskeletal and biomechanics in the foot is the arch of the foot. Flat foot, is one of the most common conditions encountered. It refers to a medical condition where the arch of the foot becomes flat. Balance is one of the most crucial coordination skills in basketball. Good dynamic balance can be achieved if athletes have normal foot arches. If the normal arch is lost, can lead to dynamic balance disturbances. This research method uses a cross-sectional analytical observational design to examine the relationship between flat foot and dynamic balance in basketball players. In this study, 26 individuals participated as research subjects. Dynamic balance measurements using the Y Balance Test (YBT). Arch of foot measurements using the wet footprint test. Data analysis in this study using the Pearson Correlation test. This research concludes that there is a significant relationship between flat foot and dynamic balance in junior high school basketball players in Denpasar. The findings of this study indicate a statistically significant relationship, as evidenced by p-values of 0.045 and 0.003 (p <0.05).